2001
DOI: 10.1254/jjp.85.335
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effect of Vitamin K2 (Menatetrenone) in Diabetic Mice

Abstract: ABSTRACT-The antinociceptive effect of vitamin K2 (menatetrenone) in diabetic mice was examined using a tail-pressure test. Intraperitoneal injection of menatetrenone (10 -100 mg/ kg) produced a dosedependent increase in the nociceptive threshold in diabetic mice. There was no significant difference between non-diabetic and diabetic mice in the menatetrenone-induced changes in the nociceptive threshold. The results suggest the therapeutical usefulness of menatetrenone for treating painful diabetic neuropathy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
(13 reference statements)
1
9
0
Order By: Relevance
“…According to evidence, high oral doses of MK-4 in human (up to 135 mg) [77-79] and in animals (up to 200mg/kg) are effective, safe and have not toxic effects [37,80,81]. Our results showed that MK-4 at the dose of 100 mg/kg/day (similar to other studies [33][34][35]) has no significant effects on mortality rate in experimental group. Thus, we injected 400 mg/kg (200 mg/kg twice in a day i.p.)…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…According to evidence, high oral doses of MK-4 in human (up to 135 mg) [77-79] and in animals (up to 200mg/kg) are effective, safe and have not toxic effects [37,80,81]. Our results showed that MK-4 at the dose of 100 mg/kg/day (similar to other studies [33][34][35]) has no significant effects on mortality rate in experimental group. Thus, we injected 400 mg/kg (200 mg/kg twice in a day i.p.)…”
Section: Discussionsupporting
confidence: 86%
“…At first, the dose of 100 mg/kg MK-4 i.p. was selected due to the previous investigations [33][34][35], however, the mortality rate of ischemic animals was high (equal I/R group). To this reason, we had to enhance the treatment dose to 400 mg/kg in two injections (200 mg/kg i.p.…”
Section: Surgical Procedures For Induction Global Cerebral I/r Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…CD-1/ICR mice demonstrate thermal allodynia following 7 to 11 days of diabetes [66][67][68][69]. Similarly, allodynia is reported in short term diabetes (2 and 4 weeks) [70,71].…”
Section: Mouse Models Of Dnmentioning
confidence: 70%
“…An underlying vasculitis with ischaemia to peripheral nerves also seemed unlikely, given that he had no cryoglobulins on repeated testing and no cutaneous signs of vasculitis 19. Another possible mechanism may be related to the inhibition of activated vitamin K, even though vitamin K has been associated with widespread physiological benefits,20 including an antinociceptive effect of vitamin K2 in diabetic mice 21. However, a study in PCD 12 animal cells showed vitamin K enhanced nerve growth factor-mediated neurite outgrowth 22.…”
Section: Discussionmentioning
confidence: 99%